Touch the Wounds : On Suffering, Trust, and Transformation. - Halík, Tomás (University of Notre Dame Press, 2023)
""In this deeply personal narrative, Tomas Halik invokes the figure of Thomas, less to affirm the importance of doubt in religious life, than to remind us that Christian faith passes through our wounds and through the reality of pain and suffering. As ever, Halik manages to offer a fresh and hopeful Christian message without condemning the secular world."" --Catherine Cornille, co-author of Christian Identity between Secularity and Plurality </h.